2009
DOI: 10.1017/s1368980009990541
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide variation of adherence to the Mediterranean diet, in 1961–1965 and 2000–2003

Abstract: Objective: The present study aimed to analyse the worldwide trends of adherence to the Mediterranean diet (MD), in 1961-1965 and 2000-2003. Design: Data were obtained from the FAO food balance sheets in two periods: 1961-1965 and 2000-2003. In order to have a sample from across the world, forty-one countries were selected. The average of available energy for different food groups was calculated for all selected countries. These values were used to evaluate the adherence to the MD through a variation of Mediter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
163
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 257 publications
(182 citation statements)
references
References 43 publications
(100 reference statements)
10
163
1
3
Order By: Relevance
“…This current piece of research followed some of the investigation categories that were identified in the Estruch et al, 2013;Valls-Pedret et al, 2015). Despite the positive effects of the Mediterranean diet on health having been cross-checked, studies evaluating dietary habits in Mediterranean countries confirm the change in Mediterranean eating behavior and show a shift towards an unhealthier type of diet (García-Closas et al, 2006;da Silva et al, 2009;Baldini et al, 2009;León-Muñoz et al, 2012;CIHEAM/FAO, 2015). Amongst the reasons explaining this change in trends the Western-type of economy is indicative, along with an urban and technology-driven culture and the globalization of food production and consumption which relate to the homogenization of food behaviors (BachFaig et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…This current piece of research followed some of the investigation categories that were identified in the Estruch et al, 2013;Valls-Pedret et al, 2015). Despite the positive effects of the Mediterranean diet on health having been cross-checked, studies evaluating dietary habits in Mediterranean countries confirm the change in Mediterranean eating behavior and show a shift towards an unhealthier type of diet (García-Closas et al, 2006;da Silva et al, 2009;Baldini et al, 2009;León-Muñoz et al, 2012;CIHEAM/FAO, 2015). Amongst the reasons explaining this change in trends the Western-type of economy is indicative, along with an urban and technology-driven culture and the globalization of food production and consumption which relate to the homogenization of food behaviors (BachFaig et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…The food balance sheet is compiled annually and is an international resource of a country's food availability during a certain period (20,22) . Food availability is derived from production, supply, different usages and wastages of food and indicates apparent consumption instead of real consumption (19,23) . Assessing the trend in availability of food components is a useful tool for evaluation of changes in dietary patterns and can applied to defining dietary patterns (24)(25)(26) .…”
Section: Databasementioning
confidence: 99%
“…In the population of Spain, a decrease in adherence to the Mediterranean diet was corroborated using FAO food balance sheets for two periods, 1961-1965 and 2000-2003 (23) . This decrease is associated with a trend towards more sedentary or unhealthy lifestyles (6,23,24) . The decrease in adherence to the Mediterranean diet affects all age groups.…”
mentioning
confidence: 99%